The Wiley-Blackwell companion to cultural geography - Johnson, Nuala Christina 1962-; Schein, Richard; Winders, Jamie (Blackwell companions to geography, 2013)
"A significantly revised new edition of this authoritative reference volume which traces the historical evolution of cultural geography through to the very latest research"--Provided by publisher.